KARAKTERISTIK FISIS KEEMPUKAN BANTAL BERBAHAN DASAR KAPUK RANDU - Rosyidatul Munawaroh; Mahardika Prasetya Aji; Sulhadi Sulhadi; Adelina Ryan Candra Dewi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The aim of this study were to determine the tenderness of a pillow from physical parameters and determine the composition of the kapok stuffing with low production costs but produces a soft pillow. The physical character tenderness of a pillow can be viewed from the force constant pillows. Five pillows with same size and density are filled  with different compotition of kapuk. the compotition are high quality with medium quality of kapuk. The results showed the mixed composition of kapok stuffing pillows affect the force constant despite having the same density. the smaller of force constan in pillow showing the decreases of pillow ability to suport a load. To keep low production costs of pillows but still produced a soft pillow, the pillow filled with kapok percentage of high quality and low quality is 50: 50.Keywords: pillow, kapok, composition, constant force.